2019
DOI: 10.2478/dcse-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrepreneurship Education in Primary School: Empowering Each Child with the YouthStart Entrepreneurial Challenges Programme

Abstract: This article provides an overview of challenge-based social entrepreneurship education in primary schools in Austria. The “YouthStart”-Programme “Empowering Each Child” is introduced as well as its impact on children. Research accompanying the programme shows that small challenges strengthen particularly the following skills and abilities of pupils: self-confidence and self-initiative, innovation, creativity, mindfulness, empathy, self-motivation and participation in society. Many of the challenges are based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 7 publications
0
21
0
3
Order By: Relevance
“…For this reason, self-efficacy has a decisive influence on behaviors, thoughts, feelings, and intrinsic motivations, activating personal conviction in the ability to perform and enabling the understanding of eventual failures as limitations that can be improved. In this way, several studies converge by positively associating self-efficacy to undertake, and programs have been developed to activate this competence [98][99][100][101][102][103]. The self-efficacy perceived as a positive belief allows performing new or complex tasks to obtain the desired results.…”
Section: Skills To Be Focused and Open To Noveltymentioning
confidence: 99%
“…For this reason, self-efficacy has a decisive influence on behaviors, thoughts, feelings, and intrinsic motivations, activating personal conviction in the ability to perform and enabling the understanding of eventual failures as limitations that can be improved. In this way, several studies converge by positively associating self-efficacy to undertake, and programs have been developed to activate this competence [98][99][100][101][102][103]. The self-efficacy perceived as a positive belief allows performing new or complex tasks to obtain the desired results.…”
Section: Skills To Be Focused and Open To Noveltymentioning
confidence: 99%
“…These studies are focused on programs that specifically target the development of ES [62,63,65,66,87], the development of business plans and models [73,74,78,91], and the promotion of skills within the scope of social entrepreneurship and sustainability [64,81,82] in the scope of agriculture [77,88] and of technologies [63,87,90]. Some specific competences also stand out, such as teamwork [63,67,73,81,86,89], self-efficacy [64,70,72,74,78,84], leadership [86,88], self-confidence [64,73,81], proactivity and initiative [64,66,84], innovation [64,66,68,84], problem solving [66,72,86], empathy [64,81], self-esteem [8...…”
Section: Characterization Of the Studiesmentioning
confidence: 99%
“…The pedagogical activities presented in the studies were quite diverse, with emphasis on classes, lectures, workshops, business simulations, group dynamics and games, visits to companies, and internship experiences in incubators, simulating the early stages of a startup. However, it was found that in the early stage of education, there were activities such as the creation of a market in the school [79], storytelling and mindfulness [64], and educational games [82]. In turn, in secondary and higher education, activities were carried out to create, develop and implement an entrepreneurial project, using business models [73,78,80], marketing studies [71,77,80,84], and finance [70,80].…”
Section: Characterization Of the Studiesmentioning
confidence: 99%
“…To map out the content of the entrepreneurship education framework, we reviewed the literature ( Fiet, 2001 ; Blenker et al, 2013 ) on three topics: (a) SDGs and CIE education ( Storey et al, 2017 ; Rashid, 2019 ); (b) creativity and social innovation ( Bisanz et al, 2019 ); and (c) educational goals. To answer the central question “How do we bridge the gap between current CIE education and SDGs?” next, we present three key aspects of the framework.…”
Section: The Sustainability-oriented Creativity Innovation and Entrmentioning
confidence: 99%